Optimizing Google Workspace in Curriculum Management and Learning Evaluation at Madrasah Aliyah Nurul Jadid - Misbahul Arifin; Tiara Nurul Annisa'; Abdullah (Dedikasi Sosial: Jurnal Pengabdian Masyarakat, 2025)
Strengthening the digital literacy of educational staff has become an urgent need in the era of technology-based educational transformation. The limited use of digital tools in curriculum management and learning evaluation remains a significant issue in many madrasahs, including Madrasah Aliyah Nurul Jadid. Therefore, this community service program was designed to enhance the digital competence of educational staff through training on optimizing Google Workspace as a supporting tool for curriculum management and learning evaluation. The program was implemented in three main stages: intensive workshops, independent implementation simulations, and continuous technical assistance, using need-based training and learning-by-doing approaches so participants could directly apply the skills they acquired to the madrasah's practical needs. The results indicate a significant improvement in participants' digital literacy, as evidenced by their ability to design digital curriculum documents, develop evaluation instruments using Google Forms, and manage learning activities through Google Classroom. Beyond individual skill enhancement, the program also strengthened the madrasah's managerial system, fostered a collaborative work culture, and accelerated the digitalization of learning administration. In conclusion, the Google Workspace optimization training proved effective in improving the digital literacy of educational staff while supporting the modernization of curriculum management in madrasahs. The sustainability plan of this program includes establishing a community of digital practice within the madrasah, developing self-learning training modules, and creating collaborative networks with other madrasahs to broaden the impact of digital transformation. This program is recommended for replication in other madrasah as a best practice and may serve as a reference for designing regional training programs.